2006
DOI: 10.1128/mcb.02353-05
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pancreatic β-Cell Proliferation Mediated by CREB Binding Protein Gene Activation

Abstract: The cyclic AMP (cAMP) signaling pathway is central in ␤-cell gene expression and function. In the nucleus, protein kinase A (PKA) phosphorylates CREB, resulting in recruitment of the transcriptional coactivators p300 and CREB binding protein (CBP). CBP, but not p300, is phosphorylated at serine 436 in response to insulin action. CBP phosphorylation disrupts CREB-CBP interaction and thus reduces nuclear cAMP action. To elucidate the importance of the cAMP-PKA-CREB-CBP pathway in pancreatic ␤ cells specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 49 publications
3
59
0
Order By: Relevance
“…This CREB protein is a key transcription factor for the maintenance of appropriate glucose sensing, insulin exocytosis, insulin gene transcription, and b-cell growth and survival (28)(29)(30). Activation of CREB, in response to a variety of pharmacological stimuli including GLP-1, initiates the transcription of target genes in the b-cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…This CREB protein is a key transcription factor for the maintenance of appropriate glucose sensing, insulin exocytosis, insulin gene transcription, and b-cell growth and survival (28)(29)(30). Activation of CREB, in response to a variety of pharmacological stimuli including GLP-1, initiates the transcription of target genes in the b-cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…IGF1 activates phosphorylation of AKT and ERK in β cells, which leads to increased cell survival and up-regulates the expression of genes including the insulin gene (34)(35)(36). Studies showed that GLP-1 improves β-cell function and increases proliferation by induction of the cAMP pathway; activation of cAMP promotes pancreatic β-cell survival by stimulating IRS-2 (29,37,38). Our work shows that in INS-1 cells, GHRH agonists elevate cell proliferation; activate three signaling pathways; increase expression of GHRH receptor, cellular insulin, and IGF1; and enhance insulin release in response to glucose challenge; GHRH antagonists completely inhibited cell proliferation induced by the agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin signaling in white adipose tissue (WAT) and liver was assessed by injection of insulin (2 U/kg) into the portal vein before excising tissue and snap-freezing for immunoblot analysis (47,48). Pancreata were fixed and stained, and islet morphometry was assessed as previously described (49). Frozen sections of gonadal white adipose tissue were stained with hematoxylin and eosin.…”
Section: Methodsmentioning
confidence: 99%